Специфіка формування молодіжних субкультур в умовах глобалізації - Сурвілайте, Д. В.; Сурвилайте, Д. В.; Survilajte, D. (My University, 2013)
The article investigates the specifics of the formation of youth subcultures globalization. Defined characteristics of youth subcultures at the present stage of global development. Analysis of the political dimension of the socio-cultural process.
Сурвілайте Д. В. Специфіка формування молодіжних субкультур в умовах глобалізації / Д. В. Сурвілайте // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 289-294.
Keywords: формування молодіжних субкультур в умовах глобалізації; характеристика молодіжних субкультур; політична складова молодіжної субкультури; соціологія молоді; формирование молодежных субкультур в условиях глобализации; характеристика молодежных субкультур; политическая составляющая молодежной субкультуры; социология молодежи; the formation of youth subcultures in the context of globalization; characteristic of youth subcultures; the political component of the youth subculture; sociology of Youth